2020
DOI: 10.4314/jsasa.v53i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Digitisation of records and archives at two selected state universities in Zimbabwe

Abstract: This study focused on the digitisation of records and archives at two selected state universities in Zimbabwe, namely Zimbabwe Open University (ZOU) and Harare Institute of Technology (HIT). The specific objective was to evaluate the legal and statutory frameworks for managing the digitisation of records and archives at the state universities. The legislative and statutory imperatives in Zimbabwe, the exponential growth in digitised records and archiving in the state universities and the lack of capacity of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Lessons learnt from other universities outside Zimbabwe, such as the University of KwaZulu-Natal (Chinyemba & Ngulube 2005), showed that some universities do have positions of university archivist to take charge of the university's memory and evidence. Surprisingly, no state university in Zimbabwe has a position of archivist in its structures (Tsvuura 2021). There are no archivists to take care of memory and evidence of all business transactions, but have positions of university librarians at the top echelon of their structures to take care of library resources for students.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lessons learnt from other universities outside Zimbabwe, such as the University of KwaZulu-Natal (Chinyemba & Ngulube 2005), showed that some universities do have positions of university archivist to take charge of the university's memory and evidence. Surprisingly, no state university in Zimbabwe has a position of archivist in its structures (Tsvuura 2021). There are no archivists to take care of memory and evidence of all business transactions, but have positions of university librarians at the top echelon of their structures to take care of library resources for students.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The adoption of ICTs in state universities brought about a paradigm shift in the creation, receipt and use of records and archives from paper to digital. However, records personnel responsible for managing digital records and archives largely lack the requisite knowledge and skills to manage such resources (Tsvuura 2021). Records personnel often remain a marginal community with some noticeable knowledge and skills gaps in managing the digital records and archives in their institutions.…”
Section: Research Problemmentioning
confidence: 99%
“…The digitisation of records and archives has been widely accepted and become an essential part of government structures in both the developed and developing countries. The adoption of digitised records and archives management in the two selected state universities has led to the decentralisation of information through networks, servers, memory sticks, databases, as well as websites in large volumes (Tsvuura 2020). This has resulted in organisational records being stored in individual employees' laptops and memory sticks, who leave the organisations carrying the records with them (Tsvuura & Ngulube 2020).…”
Section: Background and Context Of The Studymentioning
confidence: 99%
“…The adoption of digitised records and archives management in the two selected state universities has led to the decentralisation of information through networks, servers, memory sticks, databases, as well as websites in large volumes (Tsvuura 2020). This has resulted in organisational records being stored in individual employees' laptops and memory sticks, who leave the organisations carrying the records with them (Tsvuura & Ngulube 2020). A lack of university records management policies that separate official business records from personal records result in the loss of ownership and organisational records embedded in individual laptops and private email inboxes, having a great risk of being lost.…”
Section: Background and Context Of The Studymentioning
confidence: 99%
See 1 more Smart Citation